The RepID–CRL4 ubiquitin ligase complex regulates metaphase to anaphase transition via BUB3 degradation - Sang-Min Jang (Nature Portfolio, 2020)
The spindle assembly checkpoint (SAC) safeguards chromosome segregation by regulating the anaphase promoting complex/cyclosome (APC/C), allowing chromosomes to correctly attach to mitotic spindles. Here the authors reveal a role for Cullin–RING ubiquitin ligase complex 4 (CRL4) in regulating metaphase to anaphase transition via BUB3 degradation.